Pengembangan Bisnis di Kalangan Anak Muda Sumbawa - Fadli Faturrahman (Journal Economic Excellence Ibnu Sina, 2024)
Business development among young people is a growing phenomenon, especially in the creative industry and technology sectors. This research aims to explore the factors that affect the development of young people's businesses, the challenges they face, and the strategies used to overcome these obstacles. The research method used is a qualitative approach with in-depth interviews and participatory observation of 10 young entrepreneurs in Sumbawa. The results of the study show that personal motivation, such as love for the field and the desire to contribute to social change, is the main driver of young entrepreneurs to start a business. However, the biggest challenges faced are limited capital, lack of managerial skills, and difficulties in managing market risks. Digital technology is a major factor in overcoming these challenges, especially in terms of marketing and market reach. In addition, the role of mentors and entrepreneurial communities proves to be crucial for providing practical support and expanding networks. This research suggests the need to increase access to financing, more applicable entrepreneurship training, and more supportive government policies to create a conducive entrepreneurial ecosystem.